Preparation and properties of multilayer assembled polymer gel microsphere profile control agents. Issue 7 (3rd June 2019) - Zhang, Dingjun; Zhao, Wenjin; Wu, Yanfei; Chen, Zhenbin; Li, Xianru
Abstract : A polymer gel microsphere profile control agent [P(AA‐AM‐C18 DMAAC)@SiO2 ] with a multilayer assembled structure was prepared by combining multiple assembly and nanocomposite technology via inverse emulsion polymerization and precipitation polymerization using silicon dioxide (SiO2 ), acrylamide (AM), and acrylic acid (AA). The structure of the gel microsphere was characterized by SEM, FTIR, and TGA. The results indicated that the multilayer assembled polymer gel microsphere was successfully prepared. The introduction of SiO2 enhanced the strength of the profile control agent, and the outer hydrophobic association polymer octadecyl dimethyl allylammonium chloride (C18 DMAAC) changed the temperature resistance and salt resistance of the polymer by adjusting the polymer composition. Further, the influences of C18 DMAAC dosage in P(AA‐AM‐C18 DMAAC)@SiO2 at different temperatures on the water absorption ratio of the gel microsphere was studied and concluded that at C18 DMAAC to P(AA‐AM)@SiO2 mass ratio of 1.25:1, the water absorption performance of the profile control agent was optimal. Moreover, the microsphere of the P(AA‐AM‐C18 DMAAC)@SiO2 shows the characteristics of absorb water slowly at low temperatures and quickly at high temperatures. And the prepared microsphere has a certain salt tolerance, and the viscosity of the P(AA‐AM‐C18 DMAAC)@SiO2 microsphere increases slowly, so it could be used as a promising profile control agent in future. POLYM. ENG. SCI., 59:1507–1516 2019. © 2019 Society of Plastics Engineers